Genetic diversity of Lusitano horse in Brazil using pedigree information - Faria, R. S. (2018)
This study aimed to evaluate population parameters and to describe the genetic diversity of the Lusitano breed in Brazil using pedigree data. Two populations were evaluated: total population (TP) containing 18,922 animals, and reference population (RP) composed of a part of TP containing 8,329 animals, representing the last generation. The generation interval (10.1 ± 5.1 years) was in the range for horse populations. Pedigree completeness in RP shows almost 100% filling in the three most recent generations, indicating improvement in the pedigree data and accuracy of the results, and the inbreeding coefficient (4.46%) and average relatedness (5.97%) for RP, indicating control on the part of breeders. The effective population size was 89 (TP) and 90 (RP). The effective number of founders (fe) were 33 and 29, effective number of ancestors (fa) were 30 and 26, and effective number of founder genomes (fg) were 19 and 15 for TP and RP, respectively, indicating a reduction of genetic variability in the last generations. The total number of ancestors that explains 100% of the genetic diversity in the Lusitano breed in Brazil was 427 (TP) and 341 (RP). The reproductive parameters, probabilities of gene origin showing loss of variability in the last generations, and the genetic contributions of ancestors suggest the need to monitor genetic diversity over time in breeding programs to allow control of the next generations and to increase their variability.